Aplikasi Kombinasi Gaya Desain Kabuki dengan Konsep Interior Jepang Modern - Hanggoro, Shereen (Intra, 2013)
This project aims to introduce traditional Japanese dance, Kabuki as one of the components that enrich the culture of Indonesia. This center serves public facilities that have a connection with a community learning activities to learn the art of Kabuki traditional dance broadly, open, and appreciate art. The concept is movement by taking the concept of a centralized space set according with the order of importance based on the problems that arise and adapted to some of the literature and survey as guidance in solving problems to achieve the above objectives. Application presented through the plot, shapes, colors, and materials of nature in accordance with the design concept.